Principais barreiras às compras públicas sustentáveis no Brasil: uma análise a partir dos principais modelos implementados - Rezende, Raphaela Moresque Marins (2017)
The worldwide concern with actions related to sustainability has considerably increased over the last few years. In this context, several studies suggest that the uncontrolled consumption, the large generation of waste from the traditional energy production processes, the unreasonable water utilization and the use of natural resources in an inconsistent way, are factors that contribute to an acceleration of environment degradation. Thus, the concept of sustainability is becoming increasingly important, and the public administration, in turn, has been applying the Public Procurement as a tool of public policy to achieve the sustainable development. Therefore, the aim of this work is to assess the stage/outlook of PSCs in the bidding processes of three Brazilian states, São Paulo, Minas Gerais and Bahia, identifying how they introduced the following programs, and what are the ultimate barriers to the achievement of their objectives. Regarding the Brazilian scenario, several setbacks were encountered in order to implement the model in an effective way: (a) the fashion and the difficulty of changing the purchase behavior; (b) the lack of suppliers for 'sustainable' goods or services; (c) the complexity of comparing the cost/value relation of the money real appreciation; (d) the intricacy of treating the wider effects of the environmental considerations; and (e) the perception that the process and outcomes are more costly and time-consuming.